2000
DOI: 10.1093/emboj/19.11.2728
|View full text |Cite
|
Sign up to set email alerts
|

Selective instability of Orc1 protein accounts for the absence of functional origin recognition complexes during the M-G1 transition in mammals

Abstract: To investigate the events leading to initiation of DNA replication in mammalian chromosomes, the time when hamster origin recognition complexes (ORCs) became functional was related to the time when Orc1, Orc2 and Mcm3 proteins became stably bound to hamster chromatin. Functional ORCs, defined as those able to initiate DNA replication, were absent during mitosis and early G1 phase, and reappeared as cells progressed through G1 phase. Immunoblotting analysis revealed that hamster Orc1 and Orc2 proteins were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(151 citation statements)
references
References 56 publications
(119 reference statements)
11
136
2
2
Order By: Relevance
“…In order to determine if there were changes occurring at or near the time of the origin decision point (ODP), a G1-phase hallmark at which origins of replication are specified [3,39], we first examined ORC-chromatin association in mitosis and G1-phase using CHO cells synchronized with a brief nocodazole block and release. Consistent with our studies and those of others utilizing the same cell line [3,36,40], we did not detect any significant change in the amounts of ORC1, 2 or 4 in the chromatin-containing fraction during mitosis and throughout G1-phase, although a small amount of ORC1 was consistently found in the soluble fraction during mitosis (Fig. 1A).…”
Section: Orc1 2 and 4 Are Stable Proteins That Co-fractionate With Csupporting
confidence: 93%
See 1 more Smart Citation
“…In order to determine if there were changes occurring at or near the time of the origin decision point (ODP), a G1-phase hallmark at which origins of replication are specified [3,39], we first examined ORC-chromatin association in mitosis and G1-phase using CHO cells synchronized with a brief nocodazole block and release. Consistent with our studies and those of others utilizing the same cell line [3,36,40], we did not detect any significant change in the amounts of ORC1, 2 or 4 in the chromatin-containing fraction during mitosis and throughout G1-phase, although a small amount of ORC1 was consistently found in the soluble fraction during mitosis (Fig. 1A).…”
Section: Orc1 2 and 4 Are Stable Proteins That Co-fractionate With Csupporting
confidence: 93%
“…However, this model does not account for all reported results. Several laboratories do not observe fluctuation of total ORC1 levels during the mammalian cell-cycle [3,26,36,37] and in one study, protein synthesis was inhibited throughout the prophase to telophase period, with no effect on the assembly of functional pre-RCs [3]. Importantly, it has been shown that ORCdepleted Xenopus egg extracts can initiate replication within G2-phase Hela cell nuclei [38], which presumably must require the presence of mammalian ORC1 during G2-phase.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in CHO cells also observed mitotic chromosome association of CgOrc1 as well as CgOrc4 (39); however, it must be noted that Orc1 shows different cell cycle regulation in these cells compared with human cells. In CHO cells, CgOrc1 is not degraded and stays associated with chromosomes throughout the cell cycle (39); binding of CgOrc1 is weaker during mitosis and stronger in G 1 (89), and inhibition of CDK activity is necessary for CgOrc1 binding to mitotic chromosomes (90). We suggest that the difference between the CHO results and our results with human cells reflects real species-specific differences and not cell line to cell line variation because we have observed similar Orc1 dynamics in multiple human cells lines, including diploid cells.…”
Section: Discussionmentioning
confidence: 99%
“…an assay with untreated nuclear extract. The rationale for this experiment is that endogenous Orc1 is known to be rapidly degraded in vitro (29,36) with the possible consequence that the amounts of Orc1 in the S300 nuclear extracts were less than optimal for in vitro replication. Indeed, recombinant Orc1 added to the nuclear extract stimulated severalfold the standard replication reaction.…”
Section: A Nuclear Extract Is Required For Plasmid Replication In Vitro-mentioning
confidence: 99%